STATE ETHNOPOLITICS OF THE ZUNR PERIOD - Lazarovych, M. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2018)
The purpose of the article is to analyze and generalize the features and trends of the ethnonational policy of the ZUNR government in the conditions of the liberation struggle of 1918-1919. The main activities of the Ukrainian authorities to ensure the rights and freedoms of the foreign ethnic population are investigated. The legal basis of state ethnopolitics is analyzed. The attitude of national minorities to the construction of the Ukrainian state is determined. The prerequisites and the process of attracting representatives of the foreign ethnic population to practical activities for the development of Ukrainian statehood are investigated, the mechanism of national representation in government bodies is clarified, the structure and principles of their functioning are analyzed. It is summed up that the ethnopolitics of the ZUNR leadership was democratic, but the characteristic feature of the outlined chronotope was the difficult conditions caused by the aggression on the part of Poland. Therefore, many events of the Ukrainian government often remained declarative due to the impossibility of their implementation. Involvement of the foreign population to participate in the representative and executive structures of the Ukrainian government was not only an integral part of its ethno-national policy, but also an important factor in the development of the state. But national minorities, primarily Jews and Germans, showed a certain inconsistency and respecting neutrality in the Polish-Ukrainian war, significantly limited their participation in state processes.